Development and sensory analysis of Puerto Rican-style mango rum cake - Manville, Erin; Phalen, Kyle; Weber, Austin; Johnson, Kyle; Getty, Kelly J.K. (My University, 2017)
An authentic Puerto Rican mango rum cake was made with the intent of developing a microwavable dessert that could be sold as a commercial retail frozen product. To develop the cake, modifications were made to a home recipe. Modified starch and a monoglyceride were added to the cake formulation to ensure stability throughout freeze-thaw cycles and microwave reheating. A combination of C-Polar Tex 12640 modified corn starch (Cargill) and Monoglyceride GMS 90 (Cargill) were tested in the retail cake using a 3 × 3 factorial design, thus resulting in 12 combinations. The GMS 90 baker’s percentages were 0.8, 1.0, and 1.2%, whereas the C-Polar Tex 1264 baker’s percentages were 2, 3, and 4%. A panel of five food science students found C-Polar Tex 12640 at 3% and GMS 90 at 0.8% to be the ideal combination of functional ingredients for a reheatable quality comparable to a freshly baked cake. Sensory analysis was conducted to evaluate how well the retail cake would perform compared to a control cake with no added functional ingredients. A cake without starch or monoglyceride modifications was made and then frozen to be the control in the analysis. Each panelist (n=50) was given two (control and retail) microwaved cake samples and asked to complete a score sheet with questions regarding their likeness of aroma, appearance, texture, color, flavor, and overall acceptability with 1=extremely dislike and 9=extremely like. Analysis of variance was performed on SAS to determine if the functional ingredients had a significant effect on the attributes that were tested. It was determined that there were no significant differences in appearance (p=0.0993), color (p=0.5171), aroma (p=0.7853), flavor (p=0.5069), texture (p=0.3417) or overall acceptability (p=0.4280) between the control and retail cakes. The consumer scores for both products ranged from 6.9 to 7.4 which is a very acceptable rating overall. Based on the p-values it can be statistically proven that there were no significant differences between the two cakes based solely on the results of the sensory analysis. The results also indicate that the mango rum cake would be acceptable for the retail market. The sensory analysis provided a specific baseline for further testing on the modifications to get the results of equal scoring between a modified product and a non-modified product.
Keywords: Spring 2017